2014
DOI: 10.1123/jpah.2012-0075
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Physical Activity and Arterial Stiffness in Adults With Hypertension

Abstract: Habitual physical activity of all intensities is associated with reduced arterial stiffness among adults with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 0 publications
5
31
2
2
Order By: Relevance
“…There is current evidence of the beneficial effects of moderate physical activity on the arterial stiffness and on overall clinical outcomes of patients with hypertension [17]. Only 40 % of the participants in this study reported performing some type of physical activity when their blood pressure readings were high.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There is current evidence of the beneficial effects of moderate physical activity on the arterial stiffness and on overall clinical outcomes of patients with hypertension [17]. Only 40 % of the participants in this study reported performing some type of physical activity when their blood pressure readings were high.…”
Section: Discussionmentioning
confidence: 65%
“…The acute effect of physical activity on blood pressure readings is also important. It was found that a single bout of aerobic exercise reduced 24 h ambulatory blood pressure levels in long-term-treated hypertensive patients and increased the percentage of patients reaching normal ambulatory blood pressure values [17]. Aerobic exercise also has a potential role in blood pressure management of long-term-treated hypertensive both in active and sedentary obese hypertensive patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in older patients with type 2 diabetes and hypertension, a focus on increasing step counts may be a more realistic and practical option than increasing intensity, as suggested by evaluations of patient preferences [38]. Consistent with this, previous evidence suggests that even habitual physical activity is associated with decreased arterial stiffness [37,3941]. Several changes in arterial structure with aging or presence of cardiovascular risk factors may contribute to increased arterial stiffness, including fragmentation of elastin, deposition of collagen, and smooth muscle hypertrophy as a result of exposure to free radicals and inflammatory cytokines [42], and also reduced nitric oxide and increased vasoconstrictors (angiotensin, endothelin, prostaglandins) [43].…”
Section: Discussionmentioning
confidence: 87%
“…Weight loss has been shown to reduce cardiovascular risk factors including arterial stiffness 1113 . In addition, physically inactive individuals have been shown to have stiffer arterial vessels than physically active individuals 14, 15 .…”
Section: Introductionmentioning
confidence: 99%